(untitled) (Itinera, 2025)
Aestheticism was a movement that had a significant impact on early 20th-century Greek drama, as elements of it can be discerned in certain plays by some of the most prominent Greek playwrights of the period, such as Nikos Kazantzakis, Petros Nirvanas, and Konstantinos Christomanos. The movement’s female archetypes - the fatal, sensual, and dangerous woman who seduces and destroys the man, and the psychologically and physically frail and vulnerable woman - also appear in Greek theatrical works influenced by aestheticism. The present study aims to present and analyze the representation of female figures in some of these plays, as well as their reception by contemporary critics, who were strongly influenced both by feminism, socialism, and Nietzschean philosophy- dominant social and philosophical currents of the time- and by realism and ethnography, which prevailed in literary and theatrical circles.